Dominant influence of the terminal molecule of PNIPA chain on wettability - Nurul Huda,; Mohd Rashid,; Sultana, Nahida (Penerbit Universiti Kebangsaan Malaysia, 2017)
Poly(N-isopropylacrylamide) (PNIPA) brushes on silicon substrate was constructed and molecular weight and polydispersity index was controlled precisely. Molecular behavior of the PNIPA grafted surface was observed by using captive bubble contact angle method. A very interesting phenomenon of high density PNIPA grafted membrane with a chloride terminal molecule was observed. The contact angle of high density PNIPA-Cl increased sharply while the temperature rises above 32oC. But in the case of PNIPA gel surface the contact angle result decreases sharply while the temperature reaches above lower critical solution temperature (LCST). In order to identify the reason behind this abnormal behavior of PNIPA-Cl grafted membrane, the terminal chloride molecule of PNIPA chain was modified to less electronegative azide (-N3) as well as carboxylic acid (-COOH). Finally it was found that terminal molecule of high density PNIPA grafted membrane has a great influences on the wettability change of PNIPA membrane in water by changing the temperature.